A narrativa da memória sobre a ditadura civil-militar no Brasil em Tropical Sol da Liberdade, de Ana Maria Machado - Freitas, Johny Paiva (2021)
This dissertation aims to investigate the ways in which memory discourses about the civil military dictatorship in Brazil (1964-1985) are constructed during the plot of Tropical Sol da Liberdade, a novel by author Ana Maria Machado, published for the first time in 1988, three years after the official end of the military regime. Accordingly, it also seeks to analyze how the action of remembering and its ability to articulate different temporalities is transformed throughout the plot into a structuring and structuring element of the novel's own form. Thus, our initial hypothesis is that memory, transmuted by the fiction of Ana Maria Machado, not only (re) creates the dictatorial past, but also operates temporality as textuality, directly implying the way of narrating, structuring and organizing events. Therefore, our research problem goes in two confluent directions: the first one seeks to understand the potential of the act of remembering in the narrative configuration of the work under study; and the second aims to analyze the writing strategies mobilized by Ana Maria Machado to compose a complex and dense narrative about the Brazilian dictatorship. Therefore, we pay attention to the different strata that make up the writing of this work, namely: the (auto) biographical, the historical, the political, the social, which are amalgamated during the manufacture of its literary text. In order to establish the points of contact, distance and possible tensions between the different levels of composition of the novel Tropical Sol da Liberdade, some theoretical dialogues were essential, both those in the field of literary studies and those belonging to other areas of knowledge , such as History, Social Sciences and Philosophy. Among such researches, we highlight Regina Dalcastgnè (1996), Júlio Pimentel Pinto (1998; 2001), Jeanne Marie Gagnebin (2009), Ilma Socorro Gonçalves Vieira (2013), Ettore Finazzi-Agrò (2014), Régis Ramos (2014) , Eurídice Figueiredo (2017), Ricardo Barbarena (2018), Paul John Eakin (2019). It is through the choice of this interdisciplinary theoretical foundation and a comparative and tense methodology between literature and other knowledge that this research thickens its reflections and aims to contribute to future studies on the relationships between literature, history, memory and Brazilian civil-military dictatorship.